Changes in Physics Curriculum — First Results of Analysis of International Literature - Žák, Vojtěch; Kolář, Petr (Scientia in educatione, 2018)
The aim of the study is to characterize the concept of curriculum and to present selected research findings which may be useful when updating the physics curriculum of upper secondary school. The concept of curriculum may be understood in different ways. It may be seen as the contents of education, an educational plan and, most generally, as contents of all the experience pupils obtain at school and in activities connected to school. The meanings and the complexity of this concept are represented by its dimensions — dimension of aims, content, organization and methodical dimension. The curriculum exists in various forms — conceptual, project, implementation, resulting and effective. The aim of the review part was to search for studies in databases of SCOPUS and Web of Science which describe changes of physics (respectively science) curriculum and to identify methods which are used when creating new curricula. The result of the review was, among others, the finding that the number of such studies is very limited in international environment. Another identified problem is, for example, the low level of pupils’ mathematical knowledge which limits their education in physics. The investigated studies point out that the core of curriculum reforms lies only in minute changes of the existing curriculum. All these findings and some others may be used in prospective changes of physics curriculum.